A novel laparoscopy-based model for the prediction of optimal cytoreduction and prognosis of epithelial ovarian cancer in a Chinese population. (January 2021) - Tang, Xiaoyan; Zhang, Xuyin; Liu, Xin; Zheng, Tingting; Hua, Keqin; Qiu, Junjun
Abstract: Objectives: This study aimed to investigate the predictive value of laparoscopy for the prediction of optimal cytoreduction and prognosis of epithelial ovarian cancer (EOC) in a Chinese population. Study design: This study enrolled 162 EOC patients in Obstetrics and Gynecology Hospital of Fudan University from January 2015 to December 2016. All patients underwent preoperative CT scans and laparoscopic assessments. Each patient was scored according to the CT-based predictive model by Bristow and laparoscopy-based predictive model by Fagotti. The specificity, sensitivity, positive predictive value (PPV), negative predictive value (NPV) and area under the curve (AUC) of each model were calculated. The predictive scores and clinicopathologic factors were all analyzed using the Kaplan-Meier method and multivariate Cox analysis. A prognostic predictive nomogram was formulated in R software. Results: The AUCs of the laparoscopy-based predictive model and CT-based predictive model was 0.955 and 0.755 respectively. At a laparoscopic score ≥ 10, the possibility of optimal cytoreduction was 0, and the risk of unnecessary explorative attempts was 6%. Additionally, laparoscopic score, independent of residual tumor size and FIGO stage, was an independent prognostic factor for both overall survival (OS) and recurrence-free survival (RFS) in EOC. Notably, the predictive nomogram that we established further confirmed the prognostic value of laparoscopy for prognostic predictions in EOC. Conclusions: Laparoscopy has a better discriminating performance than CT in the prediction of optimal cytoreduction in EOC. Moreover, the laparoscopic score is directly correlated with the survival of EOC patients. The laparoscopic score-based nomogram we established showed good potential to predict the prognosis of EOC patients.